2018
DOI: 10.7567/jjap.57.080302
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic fractionation and characterization of magnetic nanoparticles for magnetic particle imaging

Abstract: We performed magnetic fractionation and characterization of Resovist ® magnetic nanoparticles (MNPs) for use in magnetic particle imaging (MPI). We showed that the core size of the fractionated MNPs can be controlled by adjusting the separation field. We also showed that particles with core size of approximately 27 nm are optimal for MPI applications. To obtain MNPs of an appropriate core size and a narrow size distribution, we performed combined positive and negative fractionation. In the obtained fractionate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Methods often used in order to improve the monodispersity and decrease the standard deviation of a MNP sample prepared by hydrolytic routes are those of size-sorting, including ultracentrifugation, microfiltration, size exclusion chromatography, 91,110,111 static magnetic fractionation 112 or asymmetric flow field-flow fractionation. 113,114 Fortin et al demonstrated that by the size sorting of a sample of 7.1 nm and σ of 0.37, it is possible to obtain different fractions of MNPs (from 5 to 10 nm and an improved σ of 0.1-0.2).…”
Section: Hydrolytic Methods For the Synthesis Of Mnpsmentioning
confidence: 99%
“…Methods often used in order to improve the monodispersity and decrease the standard deviation of a MNP sample prepared by hydrolytic routes are those of size-sorting, including ultracentrifugation, microfiltration, size exclusion chromatography, 91,110,111 static magnetic fractionation 112 or asymmetric flow field-flow fractionation. 113,114 Fortin et al demonstrated that by the size sorting of a sample of 7.1 nm and σ of 0.37, it is possible to obtain different fractions of MNPs (from 5 to 10 nm and an improved σ of 0.1-0.2).…”
Section: Hydrolytic Methods For the Synthesis Of Mnpsmentioning
confidence: 99%
“…2 In contrast, the magnetization of paramagnetic materials is linearly proportional to an external magnetic field. Note that this explanation omits the AC response of magnetic materials; detailed magnetic response with respect to AC magnetic fields must be considered magnetic relaxations, such as Néel and Brownian relaxations 39,42,43 . Figure 2(b) shows that the strength of the nonlinear response is represented by d 2 M/dH 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The hydrodynamic particle sizes of SA25 and SA15 were 35.9 and 62.5 nm by dynamic light scattering (DLS) 8) . The core particle size and the hydrodynamic particle size of Resovist were obtained from T. Yoshida et al 9) Fig. 3 shows the DC susceptibility characteristics of each MNP 8) .…”
Section: Measurement Samplesmentioning
confidence: 99%